The Development of the IPAER Learning Model for Improving Critical Thinking Skills in Elementary Education - Siregar, Nasyariah; Syahrial, Syahrial; Wulandari, Bunga Ayu; Sofyan, Sofyan (Universitas Muhammadiyah Magelang, 2025)
Critical thinking has become a key focus in modern education as a response to contemporary challenges. However, field observations show that students’ ability to recognize and evaluate IPAS (Science and Social Sciences Integration) content remains relatively low, indicating underdeveloped critical thinking skills. These skills can be nurtured through effective classroom instruction. In reality, many existing learning models fail to fully accommodate students’ cognitive needs. To address this gap, this study aims to develop the IPAER learning model. Employing the ADDIE research and development framework consisting of analysis, design, development, implementation, and evaluation this study collected data through observations, interviews, response questionnaires, and critical thinking tests. The findings indicate that the IPAER model is highly valid, with validation scores of 90.25% for content, 92.22% for language, 93.68% for instructional design, and 94.61% for educational technology. The model also demonstrated high practicality, with a score of 94%. Its effectiveness was evidenced by significant improvements in students’ critical thinking skills, as shown by a t-test result of p < 0.001 and high N-gain scores of 0.7604 (limited trial) and 0.7638 (large-scale trial). These results contribute to the advancement of innovative learning models that foster higher-order thinking in elementary education.